Role of virtual psychosocial interventions in coping with mental health challenges of children during the pandemic - Bhavneet Bharti; Prahbhjot Malhi (Wolters Kluwer Medknow Publications, 2021)
Background: The morbidity and mortality rates associated with the COVID-19 infection among children, fortunately, continue to be low; nevertheless, children are experiencing several pandemic-related mental health risks. Clinical Description: DK, a 9-year-old boy, was referred to the pediatrics department of a tertiary care center for compulsive oxygen saturation checking behaviors that developed a few weeks after the sudden demise of his maternal grandfather due to the COVID-19 infection. A diagnosis of adjustment disorder with emotional and behavioral problems was made as per the Diagnostic and Statistical Manual of Mental Disorder-5 criteria. Management: A comprehensive management plan was drawn out that focused on encouraging the parents to engage in productive and meaningful conversations regarding death being a permanent event in the life cycle. The child was asked to draw so that he could share his feelings and was also taught "belly breathing" that used a script of 4 counts in and 4 counts out by sharing child-orientated educational videos. The family was asked to chalk out a structured routine with time for creative artwork besides completing academic assignments. Follow-up after a month of therapy revealed an overall improvement in behavior, increased interactions with teachers and peers, and decline in compulsive checking of oxygen saturation levels. Conclusions: There is a need to expand digital treatment options for children, especially during times of public health emergencies, by using online psychoeducation resources, mental health apps, and conducting online therapy sessions.